The Relationship Between Assistance Satisfaction and Negative Affect in Long-Term Social Assistance Recipients in China: The Moderating Role of Self-Acceptance - Huang, Xinru; Chen, Hong; Li, Shanshan (Frontiers in Psychology, 2019)
Public welfare in China is less universal, comprehensive, and generous when compared with other welfare regimes, especially for individuals with occupational disease. The assistance satisfaction of Chinese pneumoconiosis patients, a typical group of long-term social assistance recipients, has been linked to diminished health and psychological well-being. Self-acceptance is theorized to promote well-being, which may buffer the negative consequences of negative emotion on assistance satisfaction. This research was conducted based on the survey data of 1,345 patients in typical mining areas of China. In addition to single-factor analysis of variance, descriptive analysis, and correlation analysis, a cluster analysis was performed to explore the profiles of participants’ ratings of assistance satisfaction with five governing subjects: government, employing unit, medical institution, welfare organization, and labor. The results were as follows. (1) Social assistance satisfaction perceived by Chinese long-term social assistance recipients was at an average level, wherein self-assistance satisfaction perception was the lowest among five dimensions. (2) The overall perception of assistance satisfaction of Chinese long-term social assistance recipients was significantly correlated with educational background and household monthly income; specifically, the participants with higher educational level or lower income were more likely to have higher assistance satisfaction perception. (3) Cross analysis showed that participants with higher assistance satisfaction were mainly from the low-high group, having a lower level of negative affect and higher level of self-acceptance. (4) The average NA level was above the scale midpoint (3.65) and negatively associated with each of the assistance satisfaction ratings. (5) The analysis yielded three distinct profiles—medium (19.26%), high (40%), and low (40.74%)—according to their degree of assistance satisfaction. Relative to the other profiles, low assistance satisfaction participants reported greater levels of NA in their daily life. However, self-acceptance moderated these effects, but no moderating effect was detected for individuals reporting greater levels of assistance satisfactory. Purpose is proved empirically a positive asset for promoting psychological adjustment in the period of receiving social assistance for Chinese long-term social assistance recipients.